Biodegradable biopolymer network structures to create delayed burst digestive release of encapsulated lipids. (February 2020) - Dekkers, B.L.; Acquistapace, S.; Donato, L.; Soulié, Virginie; Stoudmann, R.; Loussert, C.; Meyer, C.; Engmann, J.; Wooster, T.J.
Abstract: This study sought to investigate whether encapsulation of lipids in core-shell hydrogel structures of tailored shell porosity could create a delayed burst release of encapsulated lipids, and examined the underpinning mechanisms. We demonstrated that gastrointestinal digestion of core-shell structures resulted in a delay in the onset of lipid digestion, without affecting lipid digestion kinetics. Systematic increase in hydrogel protein content above 65 g/L lead to an exponential increase in digestive delay (250 min). Whilst an increase in xanthan content between 5 and 9 g/L lead to a modest decrease in digestive delay (40 min). Rheological investigations revealed a linear relationship between hydrogel storage modulus G′ and digestive breakdown delay (T1/2 ). Given that G' is directly related to hydrogel mesh size, this result suggests that the main factor controlling the timing of digestive release is the average mesh size of the outer protein hydrogel. A kinetic model was created to describe the delayed burst release behaviour of encapsulated lipids and successfully predicted the influence of shell thickness, shell protein density on the timing of gastro-intestinal release (in vitro). By combining microstructural/rheological experiments with in vitro digestive studies we have understood the main factors controlling the digestive breakdown of hierarchical biopolymer hydrogels. We could successfully miniaturise these core-shell structures so they would easily empty from the stomach whilst maintaining programmable delayed burst release. We have created a novel family of core-shell hydrogel oral dosage forms for the delivery of poorly soluble drugs and the programmed delivery of lipids within the gut. Graphical abstract: Image 1 Highlights: Encapsulation of lipids in core-shell hydrogels creates a delayed burst release. Core-shell structures delay the start of lipid digestion, without affecting the speed. A kinetic model was created to describe the delayed burst release behaviour. These new hydrogels can be used for programmed delivery within the gastrointestinal tract.